Empowering Women Entrepreneurs in MSMEs: The Role of Legal Advocacy in Overcoming Gender Barriers - Suryanti, Nyulistiowati; Yuanitasari, Deviana; Judiasih, Sonny Dewi; Assalihee, Muhammadafefee (Indonesian Journal of Advocacy and Legal Services, 2025)
The Indonesian government has recognized the importance of entrepreneurship in supporting the country's economy. Micro, Small, and Medium Enterprises (MSMEs) have become the backbone of national economic growth, with women playing a vital role in this sector. Despite their contribution, women entrepreneurs face various challenges that hinder their business development, such as limited access to capital, gender-based discrimination, legal and administrative barriers, and a lack of institutional support. These obstacles are rooted in social norms and an insufficiently responsive legal framework. This article explores how legal advocacy and institutional support can empower women MSME entrepreneurs. It argues for a more inclusive legal policy environment, examines the role of legal services such as legal aid and consultation, and discusses successful case studies of advocacy organizations helping women overcome systemic barriers. Furthermore, this paper provides practical recommendations for improving legal access and advocates for stronger collaboration between governments, legal institutions, and global advocacy networks. Through a gender-sensitive legal approach, optimizing women’s roles in MSMEs can contribute to inclusive economic growth and strengthened gender equality.